Biological treatment of domestic sewage through duckweed-cum-fish culture: a pilot-scale study - Jena, J. K.; Patro, B.; Patri, P.; Khuntia, C. P.; Tripathy, N. K.; Sinha, S.; Sarangi, N.; Ayyappan, S. (Indian Journal of Fisheries, 2011)
An aquaculture-based sewage treatment system, integrating duckweed and fish as biological components was evaluated in an urban area (Vanivihar) of Bhubaneswar city, India. The 4.5 MLD (million litres per day) system receiving continuous sewage flow comprised a sedimentation tank (0.185 ha, 3 m), three duckweed ponds (1.13 ha, depth 0.5-0.75 m) and two fish ponds (0.8 ha, depth 1.5 m). The raw sewage, after a short retention in sedimentation tank, was allowed to pass through the duckweed and fish ponds with retention periods of three and two days, respectively. The duckweed ponds with Lemna and Spirodela were provided with intermittent staggering walls for longer traversing distance of the sewage. With the doubling time of the weeds being 3-4 days, 50% of fully covered mats was harvested twice a week, keeping the residual material for further growth. The fish ponds were stocked with five carp species at a density of 10,000 fingerlings ha-1 and no additional inputs were provided. Treatment efficiency of the system was assessed through bimonthly monitoring of important chemical and microbiological parameters of water from sewage source, exit point of duckweed pond and outlet of the fish ponds for two years, during August, 2003 - August, 2005. The observations revealed mean reduction levels of 88% ammonia, 85% nitrite, 55% nitrate, 71% phosphate, 79% biological oxygen demand (BOD), 75% chemical oxygen demand (COD) and 70% total suspended solids from the source to the outlet. Similarly, aerobic heterotrophs, total coliforms, faecal coliforms, faecal streptococci, Salmonella and Shigella population recorded reduction levels of 66.8, 85.7, 92.0, 92.4, 99.4 and 85.6% respectively.